Construction of the national fitness public service satisfaction model in China based on American Customer Satisfaction Index - Fengqin Tian; Jieyou Zhou; Fei Liu (PLoS ONE, 2025)
Objective The national fitness initiative in China is a strategic priority, public satisfaction is a key metric for evaluating the effectiveness of public services. The American Customer Satisfaction Index (ACSI) model has proven a robust tool for evaluating satisfaction with public services. The objective of study was to construct a satisfaction model for national fitness public services in China based on the ACSI framework and to explore the complex relationships among its components. Methods Evaluation dimensions and an item pool were carefully developed by referencing the ACSI model and relevant academic literature. After a panel of experts assessed the initial items pool, the study formed the questionnaire to distribute the residents in Guangzhou, a total of 1,133 valid responses were collected. Data analysis was conducted using SPSS 22.0 and AMOS 16.0 software to evaluate the reliability and validity of the measurement model, the goodness-of-fit of the structural model, and analyze the statistical significance of each path coefficient. Results Public expectation does not directly influence satisfaction (path coefficient 0.039, p = 0.103), it exerts a significant and direct influence on perceived quality (path coefficient 0.445, p = 0.003), which in turn demonstrably shapes public satisfaction (path coefficient 0.403, p = 0.005). Perceived quality also directly influences perceived value (path coefficient 0.735, p = 0.006), which in turn significantly impacts public satisfaction (path coefficient 0.554, p = 0.003). Public satisfaction directly and significantly influences both public complaints (path coefficient 0.395, p = 0.003) and public trust (path coefficient 0.699, p = 0.003). Conclusion Perceived quality is the most critical factor influencing public satisfaction, which subsequently affects public complaints and trust. Fitness service providers should consistently improve service quality, aligning actual service delivery with public expectations, and enhancing the perceived value for the public. These efforts will bolster the public’s satisfaction level.